DNA Repair- An Update 2019
DOI: 10.5772/intechopen.82642
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of DNA Base Excision Repair by Protein-Protein Interactions

Abstract: The system of base excision repair (BER) evolved to correct the most abundant DNA damages in mammalian cells is the most essential for maintaining the genome integrity. The multistep BER process involves several enzymes and protein factors functioning in a coordinated fashion that ensures the repair efficiency. The coordination is facilitated by the formation of protein complexes stabilized via either direct or indirect DNA-mediated interactions. This review focuses on direct interactions of proteins participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…During BER, DNA intermediates are bound by one or several BER enzymes (BER mechanism is reviewed extensively, see [78][79][80][81] for example). Thus, a question arises: how NER can be involved in oxidative damage repair?…”
Section: Ner Impact In Oxidative Lesions Repairmentioning
confidence: 99%
“…During BER, DNA intermediates are bound by one or several BER enzymes (BER mechanism is reviewed extensively, see [78][79][80][81] for example). Thus, a question arises: how NER can be involved in oxidative damage repair?…”
Section: Ner Impact In Oxidative Lesions Repairmentioning
confidence: 99%
“…The efficient repair of damaged DNA via the multistep process of each of the subpathways requires the coordinated action of enzymes catalyzing the sequential individual reactions [2][3][4]. Coordination is facilitated by multiple protein-protein interactions, reviewed previously [13,44]. Physical interaction and functional interplay between two major BER enzymes, APE1 and Polβ, were shown by various [13,31,38,41,45].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA polymerase β (Polβ) is the smallest enzyme of the BER pathway. Several enzymes involved in the BER pathway interact with Polβ like DNA glycosylase, APE, PKNP, FEN1, PARP, XRCC1, [ 8 ] etc. In our previous study, we reported an ovarian cancer-specific mutation in the DNA Polβ, with the deletion in exon number 11–13, which could be detectable at an earlier stage of cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%